Decreased Taxon-Specific IgA Response in Relation to the Changes of Gut Microbiota Composition in the Elderly - Sugahara, Hirosuke; Okai, Shinsaku; Odamaki, Toshitaka; Wong, Chyn B.; Kato, Kumiko; Mitsuyama, Eri; Xiao, Jin-Zhong; Shinkura, Reiko (Frontiers in Microbiology, 2017)
Gut microbiota is known to change with aging; however, the underlying mechanisms have not been well elucidated. Immunoglobulin A (IgA) is the dominant class of antibody secreted by the intestinal mucosa, and are thought to play a key role in the regulation of the gut microbiota. T cells regulate the magnitude and nature of microbiota-specific IgA responses. However, it is also known that T cells become senescent in elderly people. Therefore, we speculated that the age-related changes of IgA response against the gut microbiota might be one of the mechanisms causing the age-associated changes of gut microbiota composition. To prove our hypothesis, faecal samples from 40 healthy subjects (adult group: n = 20, an average of 35 years old; elderly group: n = 20, an average of 76 years old) were collected, and the gut microbiota composition and the response of IgA to gut microbiota were investigated. The relative abundance of Bifidobacteriaceae was significantly lower, whereas those of Clostridiaceae, Clostridiales;f__ and Enterobacteriaceae were significantly higher in the elderly group than in the adult group. There was no significant difference in the faecal IgA concentration between the adult and elderly groups. However, the taxon-specific IgA response to some bacterial taxa was different between the adult and elderly groups. To evaluate inter-group differences in the taxon-specific IgA response to each bacterial taxon, the IgA-indices were calculated, and the IgA-indices of Clostridiaceae and Enterobacteriaceae were found to be significantly lower in the elderly group than the adult group. In addition, Clostridiales;f__ and Enterobacteriaceae were significantly enriched in the IgA+ fraction in the adult group but not in the elderly group, whereas Clostridiaceae was significantly enriched in the IgA- fraction in the elderly group but not in the adult group. Some species assigned to Clostridiaceae or Enterobacteriaceae are known to be pathogenic bacteria. Our results suggest the possible contribution of decreased IgA response in the increased abundance of bacterial taxa with potential pathogenicity in the intestinal environment of the elderly. Our findings contribute to the understanding of the regulatory factor for the changes in the gut microbiota composition with aging.